A Feasibility study on Bacterial Cardiolipin Antigen Kit - Axalan, Maria Hestia; Manansala, Maria Carmela; Medina, Jason James; Reyes, Roberto (College of Engineering, 1996)
Department of Health records show that reported cases of syphilis infection are found to steadily increase with time. Rogelio S. Cruz of the Centro Escolar University and Gloria de Castro-Bernas, Ph.D of the Research Center for Natural Sciences of the University of Santo Tomas have developed a kit proven to have several advantages over the commercially prepared diagnostic kits for syphilis. The diagnostic kit is called the Bacterial Cardiolipin Antigen Kit or the BCA Kit. The BCA Kit makes use of a locally prepared cardiolipin extracted from E.coli bacterial isolated from ordinary water samples in the country. The reading of diagnostic results with this kit will need an ELISA or microplate reader, thus giving out quantifiable results. After having examined the production of the said kit, venturing into the project is deemed to be economically and socially feasible for the following reasons: 1. The BCA kit is offered for the use of 1) government and private hospitals under the secondary or tertiary categories; 2) diagnostic clinics; and 3) blood banks. Thirty-percent (30%) of the present statistics of secondary and tertiary hospitals is estimated to be captured by the product that yields a demand of 2,038 kits for the starting year. Based on this study, there is a substantial amount of market and a projected steadily increasing need for the product for the first five years of operation. 2. The project that will be located in the confines of the Research Center for Natural Sciences of UST in España, Manila, will entail an amount of P3,718,378.00. The whole project was found to require materials, supplies, machinery, equipment, and technology that are readily available and accessible. 3. The financial statements and ratios derived for the first five years of operation show that the project is profitable, with a net income of P 635,271.00 for the first year. Moreover, the project is sure to give desirable results as shown by: 1) a one-year-and-nine-months payback period; 2) an internal rate of return (IRR) of 59.68%; and 3) a net present value of (NPV) P13,057,601.00 . With these findings, the Development Bank of the Philippines could extend financial assistance for the production activities of the company. 4. The society and economy could derive net positive gains from the project in terms of employment and income generation, exportation, local products and resources utilization, pricing, and tax generation. The firm's ownership is a general partnership for ease of formation, practice of profession, and flexibility of operations. The firm will be employing a total of ten (10) personnel, sic of which are full0time employees. In this regard, the proposed organizational setup is designed to work at the optimal level possible.